FACTORS AFFECTING THE DEVELOPMENT OF INDEPENDENCE OF CHILDREN AGED 2-3 YEARS AT TPA X - Adhani, Dwi Nurhayati; Mayangsari, Dewi; Susilawati, Susilawati (LP2M IAI Al-Khairat Pamekasan, 2025)
Early childhood autonomy is a condition where children are ready to do everything without the help of other people, including being able to be left by their parents for a while, choosing their activities, being able to use the toilet but still being helped or reminded, eating and drinking by themselves. Autonomy can be formed from two factors: 1) Internal factors, including physiological and psychological conditions, and 2) External factors, including the environment, feelings of love and affection, parenting patterns in the family, life experiences and habits. Besides being cared for at home, young children are also cared for in Daycare (TPA) because their parents work. This research aims to describe the factors that influence the development of autonomy in children aged 2-3 years in daycare settings. The type of research used is qualitative, using Miles and Huberman data analysis techniques. The stages of data analysis include data reduction, data presentation and conclusion. Data collection techniques include observation, interviews, and documentation. The research subjects are children aged 2-3 years who were entrusted to the TPA. The research results show that the factors that influence the development of independence in children aged 2-3 years at TPA to try it yourself in stages, fulfil feelings of love and affection, encourage children to communicate, and implement a democratic parenting style. Experiences that are influential in developing autonomy are playing and interacting experiences. In TPA, the dominant factors that influence the development of children's independence are habituation accompanied by direction from caregivers and adjusting to the child's character and mood.